Learning styles and volitional strategies in upper secondary school students - Juárez Díaz, Catalina; Rodríguez Guardado, María del Socorro (Journal of Learning Styles, 2021)
High school students drop out their studies due to lack of motivation, identity with their institutions and way of being instructed. For the necessary educational training of students, it is not enough to consider the cognitive aspects; it is also required to develop the motivational and affective aspects of their learning style. So that students can persist in the face of difficulties and challenges to achieve their academic goals. The objective of this quantitative, non-experimental, cross-sectional, descriptive study with a sample of 218 high school was to identify the volitional strategies that students use according to their learning style. It intended to answer the research questions: What is the predominance of learning styles of NMS students? What are the volitional strategies used by students? What are the volitional strategies that predominate in each of the learning styles? The results showed a predominance of the theoretical style. Students employ more frequently the negative base incentive strategy. The researchers concluded that there is much work to be done in research focused on the study of volitional strategies and learning styles that refer to people's integral development.